2021
DOI: 10.1186/s13643-021-01699-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of meditation on length of telomeres in healthy individuals: a systematic review

Abstract: Background Meditation-based practices have been suggested to result in many biological benefits which include reduction of attrition of telomeres, the protective nucleotide-protein complexes at termini of eukaryotic chromosomes. This systematic review evaluated the effects of meditation on telomere length (TL) in healthy adults. Methods Randomized controlled trials (RCTs) and observational studies conducted to determine the effects of meditation on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…To identify relevant studies, we used five electronic databases (PsychINFO, Pubmed, Clinical Key, CINHAL Complete, and Google Scholar) as well as the reference lists of the three previously published reviews (Dasanayaka et al, 2021;Dunn & Dimolareva, 2022;Schutte & Malouff, 2014;Schutte et al, 2020). For the electronic database search, we employed a multi-tiered search strategy.…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify relevant studies, we used five electronic databases (PsychINFO, Pubmed, Clinical Key, CINHAL Complete, and Google Scholar) as well as the reference lists of the three previously published reviews (Dasanayaka et al, 2021;Dunn & Dimolareva, 2022;Schutte & Malouff, 2014;Schutte et al, 2020). For the electronic database search, we employed a multi-tiered search strategy.…”
Section: Search Strategy and Study Selectionmentioning
confidence: 99%
“…Risk of bias assessments was adopted from prior reviews (Dasanayaka et al, 2021;Dunn & Dimolareva, 2022) for studies, which had been included in these reviews. Independent assessments were conducted for studies, which had not been rated before.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…If we consider several recent publications within the field of meditation research, we can start to articulate the confusion that surrounds the definition of meditation. Many investigators state that they study meditation only involving a specific techniques, such as FA (Dasanayaka et al, 2021;Zhang et al, 2021). In other studies different forms of meditation have been lumped together without any justification of the implicit claim that they have something essential in common (Haider et al, 2021;Sumantry and Stewart, 2021).…”
Section: Challenges For Defining Meditationmentioning
confidence: 99%
“…A systematic review, which investigated the effects of meditation on telomere length, found positive effects on telomere length of two randomized controlled trials and three case control studies of high and moderate quality, although only one randomized trial and one case control study obtained statistical significance [108].…”
Section: Stress Management and Psychological Interventionsmentioning
confidence: 99%